Controlling a non-homogeneous Timoshenko beam with the aid of the torque - Sklyar, Grigory M.; Szkibiel, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
Considered is the control and stabilizability of a slowly rotating non-homogeneous Timoshenko beam with the aid of a torque. It turns out that the beam is (approximately) controllable with the aid of the torque if and only if it is (approximately) controllable. However, the controllability problem appears to be a side-effect while studying the stabilizability. To build a stabilizing control one needs to go through the methods of correcting the operators with functionals so that they have finally the appropriate form and the results on C0-continuous semigroups may be applied.
Keywords: Timoshenko beam; rotating beam control; approximate control; stabilizability